2004
DOI: 10.1080/0267152042000295465
|View full text |Cite
|
Sign up to set email alerts
|

Schools for the 21st century: the national debate on education in Scotland

Abstract: In 2002, the Scottish Executive Education Department launched a national debate on schools for the 21st century. The debate elicited over 1500 responses and it is estimated that 20,000 people took part. This paper describes the main themes arising from the debate, highlighting the support for comprehensive education and the high level of trust in the quality and professionalism of teachers. The agenda for change was in terms of greater flexibility and choice in the school curriculum and of the need for well-bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 3 publications
0
24
0
Order By: Relevance
“…Much policy development is founded on the priorities that emerged from the National Debate on Education held in 2002 (Munn et al 2004). But in the context of the discussion here the first key point is that the incorporation of a research and enquiry element in teaching and teacher education is well established, at least in terms of formal policy.…”
Section: The Context For Teacher Education In Scotlandmentioning
confidence: 99%
See 1 more Smart Citation
“…Much policy development is founded on the priorities that emerged from the National Debate on Education held in 2002 (Munn et al 2004). But in the context of the discussion here the first key point is that the incorporation of a research and enquiry element in teaching and teacher education is well established, at least in terms of formal policy.…”
Section: The Context For Teacher Education In Scotlandmentioning
confidence: 99%
“…In the Scottish context, the Scottish Higher Education Funding Council and the Scottish Executive Education Department announced their own scheme designed to address perceived weakness in the Scottish universities' performance in research in education as assessed by the UK Research Assessment Exercise (RAE) in 2001, since no higher education institution in Scotland received a top rating at the level of 5 or 5* in 2001 for research in education. The Applied Educational Research Scheme (AERS) was awarded £2 million over a five-year period from 2004 to 2009 and had two principal aims: to build research capacity in education in Scotland; and to use that capacity to carry out worthwhile research directed towards the national priorities for education in Scotland, as described by Munn et al (2004). Whitty (2006) has drawn the distinction between two terms used to describe research in education by referring to 'educational research' as research concerned in one way or another with improving policy and practice while the term 'education research' should be used more broadly to characterise the whole field.…”
Section: Introductionmentioning
confidence: 99%
“…In much of the research undertaken on behaviour in schools, teachers have regularly reported feeling concerned about discipline; about how to maintain and develop effective behaviour management strategies; about how to engage with home and family, especially where there are difficulties at home; and about trying to balance the rights of the individual and the group within the classroom (Munn, 2002;Munn et al, 2004;Wilkin et al, 2006). It is particularly interesting that although corporal punishment has been abolished for longer in the United Kingdom than in South Africa and much effort has been directed to 'improving behaviour', these issues remain central to many teachers' daily professional lives.…”
Section: Discussionmentioning
confidence: 99%
“…After some initial turbulence, there has been considerable stability in the institutional structures of secondary schooling and in local authority governance. This has been matched by a general civic commitment to comprehensive education, evidenced in the National Debate of 2002-03 (Munn et al, 2004). Around 93.6% of Scottish secondary pupils attend state comprehensive schools,[1] with only around 15% attending a school outwith the designated catchment area, although this figure rises considerably in and around Scotland's major cities.…”
Section: Introductionmentioning
confidence: 99%